Assessment of patellofemoral pain syndrome in women - doi:10.5020/18061230.2011.p5 - Pereira Júnior, Altair Argentino (2012)
Objective: To assess women diagnosed with patellofemoral pain syndrome (PFPS). Methods: A descriptive study held with 40 women aged between 18 to 40 years, with defined medical diagnosis of PFPS. We conducted the verification of knee function using the Lysholm scale; kinetic- functional and radiologic assessment; determination of body mass index (BMI) and investigation of physical activity level by the International Physical Activity Questionnaire. Results: There was a predominance of genu valgum, internal femoral rotation and high lateral patella. The level of physical activity was less than 150 minutes in 21 (52.5%)of the sample. Overweight was found in 16 (40%)and knee function classified as unsatisfactory in 31 (77.5%)of the participants. Conclusion: The study participants had similar kineticfunction alterations and presence of overweight. The PFPS commits the knee function, hindering the activities of daily living and sports